(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Effective collaboration between laboratory, radiology, and nursing teams is crucial for delivering high-quality patient care. Timely communication of lab and radiology results is a key factor impacting nursing decisions and patient outcomes. This review explores challenges in lab-nursing and radiology-nursing collaboration, focusing on delayed results, and discusses strategies to enhance integration in Saudi Arabia’s healthcare settings. By identifying barriers and proposing solutions, this paper aims to contribute to improved patient care and safety.